2006
DOI: 10.1007/s11064-006-9091-1
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Creatine Kinase Activity Caused by Electroconvulsive Shock

Abstract: Although several advances have occurred over the past 20 years concerning the use and administration of electroconvulsive therapy to minimize side effects of this treatment, little progress has been made in understanding its mechanism of action. Creatine kinase is a crucial enzyme for brain energy homeostasis, and a decrease of its activity has been associated with neuronal death. This work was performed in order to evaluate creatine kinase activity from rat brain after acute and chronic electroconvulsive shoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…The effect of electroconvulsive shock (an animal model for electroconvulsive therapy) showed increased activities of mitochondrial respiratory chain complexes II and IV [64], and inhibition on creatine kinase activity in brain of rats [65].…”
Section: Depressionmentioning
confidence: 99%
“…The effect of electroconvulsive shock (an animal model for electroconvulsive therapy) showed increased activities of mitochondrial respiratory chain complexes II and IV [64], and inhibition on creatine kinase activity in brain of rats [65].…”
Section: Depressionmentioning
confidence: 99%
“…Some studies showed that reductions of regional cerebral blood flow or regional cerebral metabolic rate occur after ECT, especially in cerebral cortex, suggesting a possible suppression of brain activity [20], associated with better clinical outcome [21]. In this context, we have recently shown that acute and chronic ECS decreased creatine kinase activity in brain of rats [22].…”
Section: Discussionmentioning
confidence: 91%
“…Different groups of rats (n = 8 each 33,34 ) were administered intraperitoneally with saline or different doses of ketamine (5, 10 and 15mg/kg) or imipramine (10, 20 and 30mg/kg) 60 minutes before the test session (forced swimming test). The range of doses of ketamine employed in this work was chosen based on a previous study, which reported an increase in spontaneous locomotor activity at 25mg/kg, while no changes were observed at 10mg/kg.…”
Section: Acute Administration Of Ketamine and Imipraminementioning
confidence: 99%
“…[27][28][29][30][31] We have recently showed that brain CK activity is inhibited by antipsychotics (haloperidol and olanzapine), 32 in animal models of neuropsychiatry disorders, such as bipolar disorder 33 and after electroconvulsive shock. 34 Brain and other high-energy consuming tissues are more susceptible to reduction of energy metabolism. Neuropsychiatry disorders, such as schizophrenia, depression and bipolar disorder have been related to dysfunction in brain metabolism.…”
Section: Introductionmentioning
confidence: 99%